2023
DOI: 10.1002/ijc.34465
|View full text |Cite
|
Sign up to set email alerts
|

Absence of terminal deoxynucleotidyl transferase expression in T‐ALL/LBL accumulates chromosomal abnormalities to induce drug resistance

Abstract: T-acute lymphoblastic leukemia/lymphoma (T-ALL/LBL) is a malignant neoplasm of immature lymphoblasts. Terminal deoxynucleotidyl transferase (TDT) is a templateindependent DNA polymerase that plays an essential role in generating diversity for immunoglobulin genes. T-ALL/LBL patients with TDT À have a worse prognosis. However, how TDT À promotes the disease progression of T-ALL/LBL remains unknown. Here we analyzed the prognosis of T-ALL/LBL patients in Shanghai Children's Medical Center (SCMC) and confirmed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…26 Another study reported that TdT-negative T cell acute lymphoblastic leukemia/lymphoma (T-ALL/LBL) patients had poor therapeutic responses; TdT loss decreased apoptosis, induced the accumulation of chromosomal abnormalities and tolerance to abnormal karyotypes. 27 DNTT loss might modulate the DSBs repair response to InO and result in increased tolerance to InO-induced DNA damage, leading to InO resistance. We observed decreased DNTT RNA expression in patient samples at post-InO ( P =0.03, mean of different -1.19 log2[counts per million], 95% CI [-2.23, -0.11], Supplemental Figure 3D); no post-InO acquired DNTT mutations were identified in this dataset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Another study reported that TdT-negative T cell acute lymphoblastic leukemia/lymphoma (T-ALL/LBL) patients had poor therapeutic responses; TdT loss decreased apoptosis, induced the accumulation of chromosomal abnormalities and tolerance to abnormal karyotypes. 27 DNTT loss might modulate the DSBs repair response to InO and result in increased tolerance to InO-induced DNA damage, leading to InO resistance. We observed decreased DNTT RNA expression in patient samples at post-InO ( P =0.03, mean of different -1.19 log2[counts per million], 95% CI [-2.23, -0.11], Supplemental Figure 3D); no post-InO acquired DNTT mutations were identified in this dataset.…”
Section: Resultsmentioning
confidence: 99%
“…26 Another study reported that TdT-negative T cell acute lymphoblastic leukemia/lymphoma (T-ALL/LBL) patients had poor therapeutic responses; TdT loss decreased apoptosis, induced the accumulation of chromosomal abnormalities and tolerance to abnormal karyotypes. 27 Moreover, loss of CHEK2, the crucial G1/S checkpoint gene, led to InO resistance (Supplemental Figure 3A and 3C). This supported the observation and hypothesis from patient data (Figure 4D) that tumor cells resisted InO by compromise of the G1/S DNA damage checkpoint.…”
Section: Genome Wide Crispr Screening Identified Ino Resistance and S...mentioning
confidence: 97%
“…The poor prognosis of DT-negative T-ALL patients was associated with abnormal DNA aggregation leading to drug resistance (e.g. VP16, MTX) [32,33], and chidamide may be able to overcome conventional chemotherapy resistance based on its chromatin-releasing activity. 4) Chidamide combined with chemotherapy regimens can effectively decrease MRD in T-ALL patients with NOTCH1 mutation [21].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical treatment of T-ALL currently relies on traditional chemotherapy modalities. However, T-ALL is not very responsive to current chemotherapeutic agents and is prone to developing drug resistance [3,4]. Additionally, T-ALL has a high relapse rate in the central nervous system [5], and traditional chemotherapeutic drugs are not effective in inducing remission.…”
Section: Introductionmentioning
confidence: 99%